2020
DOI: 10.1175/jamc-d-19-0304.1
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Flow Fields in Complex Terrain with WRF-LES: Sensitivity Assessment of Different PBL Treatments

Abstract: A multiscale modeling study of a real case has been conducted to explore the capability of WRF-LES over the Xiaohaituo Mountain (a game zone for the Beijing-2022-Winter-Olympic-Games). Comparing WRF-LES results with observations collected during the MOUNTAOM (MOUNtain Terrain Atmospheric Observations and Modeling) field campaign, it is found that at 37 m resolution with LES settings, the model can reasonably capture both large-scale events and microscale atmospheric circulation characteristics. Employing SRTM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…In addition, Rai et al (2019) found that performance of the WRF LES is less sensitive to the PBL scheme used in the parent domain than it is to the sub-grid-scale turbulence parameterization used in the LES domain. A similar conclusion was found by Liu et al (2020) in simulating flows over complex terrain. Thus, it was decided to use the MYNN scheme, since the simulation period spanned the transition from stable nocturnal morning boundary layer to daytime convective boundary layer.…”
Section: Model Configurationsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, Rai et al (2019) found that performance of the WRF LES is less sensitive to the PBL scheme used in the parent domain than it is to the sub-grid-scale turbulence parameterization used in the LES domain. A similar conclusion was found by Liu et al (2020) in simulating flows over complex terrain. Thus, it was decided to use the MYNN scheme, since the simulation period spanned the transition from stable nocturnal morning boundary layer to daytime convective boundary layer.…”
Section: Model Configurationsupporting
confidence: 86%
“…Muñoz-Esparza et al (2014) demonstrated that the absence of fully spun-up turbulence in LES can lead to an imbalance between the subgrid scale and resolved scales of motion that not only degrades the turbulence intensity estimates but can also result in a spurious wind speed profile. Markowski and Bryan (2016) have reported that LESs without properly developed turbulence produce unrealistic near-surface vertical wind profiles with excessive vertical wind shear. Muñoz-Esparza and have shown that the distance required for turbulent motions to fully develop is related to the ratio of the convective velocity scale and the horizontal mean wind during convective daytime conditions.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, researchers have used LES approximation to study specific problems such as air pollution dispersion in urban street canyons [8][9][10], flow distortion caused by wind turbines [11][12][13], large fires [14,15] or cloud and precipitation processes development [16][17][18][19]. Many other studies have used real case LES to simulate atmospheric flows in complex terrain areas [20][21][22] where grid sizes of few hundreds of metres are needed to resolve the terrain elevation and LES approximation is required. Other authors suggested the need to use LES to resolve small-scale turbulent processes in complex terrain such as downslope windstorms [23], low-level turbulence and rotors [24,25], precipitation dynamics [26][27][28][29] or other small scale processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of previous LES studies are conceived as idealised theoretical studies (e.g., [32][33][34][35]), allowing to isolate specific atmospheric phenomena, while others are designed as real case studies, which need to be compared with proper high-resolution observational data sets. Some recent case studies consider simulation periods of one or few days (e.g., [22,36,37]) which allows sensitivity tests varying the model configuration but restricts the verification process and hampers the evaluation of the general quality of the simulations. In this paper, we report a large eddy simulation using the WRF-LES system spanning 25 days during a field experimental campaign.…”
Section: Introductionmentioning
confidence: 99%
“…Those two uncertainties propagate in the simulated ambient concentrations. For instance, urban zones in complex terrain pose a great challenge to current meteorological modeling tools [ 9 ], and the low-wind, stable meteorological conditions that drive air pollution episodes are difficult to be represented in current models [ 10 ]. In a review of photochemical and PM 2.5 dispersion modeling applications in the US and Canada [ 11 ], the percentage of observed variance explained by the dispersion model (r 2 ) varies between 0.2 and 0.6 for hourly ozone and between 0.1 and 0.6 for PM 2.5 and its major species.…”
Section: Introductionmentioning
confidence: 99%